The Efficiency of Employing Cable Claim in Education Language - Ziyoda Mukhamedova; Muxabbat Yusupova (Al-Qanṭara, 2022)
Abstract Technology usage has become a crucial factor in learning English in and out of the classroom. Nowadays, English classroom utilizing digital technology application. Digital technologies have been utilized to improve and help teaching and learning the language. Digital technologies help educators to adapt modern teaching methods, therefore, improve the process of teaching and learning the English language. This paper investigates the effect of using digital technology(Telegram) on EFL students’ vocabulary learning. 40 Arab high school pre-intermediate EFL students at Arabic International School in Kuala Lumpur were selected. Using a quasi-experimental design, the data was collected through a placement test, pre-post-test. Students were divided into control and experimental groups. The experimental group received their lessons through Telegram. However, the control group practised conventional teaching methods. The data of the experimental post-test showed that Telegram is an effective teaching tool that motivates students to learn vocabulary enjoyably. Implications and recommendations are drawn at the end of the paper.